Microwave heat treatment of glutinous rice emping - Mohd Dom, Zanariah; Shamsudin, Rosnah; Noordin, I. (Rynnye Lynn Resources, 2024)
This study aimed to determine the new cooking method of emping by using a microwave oven at different temperatures (230°C, 240°C, 250°C) and time taken (3.30 min, 4.00 min, 4.30 min, 5.00 min, 5.30 min). Next, to analyze the physicochemical and frictional properties during the transformation from glutinous paddy (Siding) at 90 days of maturity to emping. The suitable cooking parameter was at a temperature of 250oC and 4.30 minutes. The change in length from glutinous paddy to emping was increased from 10.61 mm to 11.01 mm. For width, the change from glutinous paddy to emping was 2.51 mm to 3.14 mm. However, the thickness from glutinous paddy to emping was changed from 1.93 mm to 1.12 mm. The bulk density and true density of emping are lower than glutinous paddy. Lastly, the value of emping was higher for porosity and angle of repose compared with glutinous paddy.